2021
DOI: 10.1177/21501351211009768
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Reoperation After Arterial Switch Operation

Abstract: Objective: The timing and nature of and risk factors for reoperation after the arterial switch operation in the setting of d-transposition of the great arteries requires further elucidation. Methods: A total of 403 patients who underwent arterial switch operation from 1986 to 2017 were reviewed. Institutional preference was for pulmonary artery reconstruction using a pantaloon patch of fresh autologous pericardium. The targets for coronary artery reimplantation were identified by intermittent root distension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In others' experience, the use of pericardium pretreated with glutaraldehyde, irrespective of its concentrations, was associated with the development of PA stenosis postoperatively, and the authors recommended using a pantaloon patch of fresh autologous pericardium to minimize PA reinterventions. 16 Residual stenosis of the PA can be progressive. Indeed, a previous report 17 has shown that PA stenosis was more frequent and more severe in the patients who had undergone reintervention before.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In others' experience, the use of pericardium pretreated with glutaraldehyde, irrespective of its concentrations, was associated with the development of PA stenosis postoperatively, and the authors recommended using a pantaloon patch of fresh autologous pericardium to minimize PA reinterventions. 16 Residual stenosis of the PA can be progressive. Indeed, a previous report 17 has shown that PA stenosis was more frequent and more severe in the patients who had undergone reintervention before.…”
Section: Commentmentioning
confidence: 99%
“…In others’ experience, the use of pericardium pretreated with glutaraldehyde, irrespective of its concentrations, was associated with the development of PA stenosis postoperatively, and the authors recommended using a pantaloon patch of fresh autologous pericardium to minimize PA reinterventions. 16…”
Section: Commentmentioning
confidence: 99%
“…7 Along with prolonged CPB time, it has been shown that more complex anatomy—including Taussig-Bing anomaly—is a risk factor for any reoperation. 8…”
Section: Commentmentioning
confidence: 99%
“…7 Along with prolonged CPB time, it has been shown that more complex anatomy-including Taussig-Bing anomaly-is a risk factor for any reoperation. 8 Studies show that other preoperative characteristics such as timing of the ASO may affect the outcomes and mortality of patients following the ASO. 9 This led us to hypothesize that age at the ASO, weight at the ASO, or other preoperative factors may be associated with reintervention, but the data did not find any associations with these preoperative factors.…”
Section: Commentmentioning
confidence: 99%